New peptide derived antimalaria and antimicrobial agents bearing sulphonamide moiety - D. I. Ugwuja; U. C. Okoro; S. S. Soman; R. Soni; S. N. Okafor; D. I. Ugwu (Taylor & Francis Group, 2019)
Fourteen novel dipeptide carboxamide derivatives bearing benzensulphonamoyl propanamide were synthesized and characterized using 1H NMR, 13C NMR, FTIR and MS spectroscopic techniques. In vivo antimalarial and in vitro antimicrobial studies were carried out on these synthesized compounds. Molecular docking, haematological analysis, liver and kidney function tests were also evaluated to assess the effect of the compounds on the organs. At 200 mg/kg body weight, 7i inhibited the multiplication of the parasite by 81.38% on day 12 of post-treatment exposure. This was comparable to the 82.34% reduction with artemisinin. The minimum inhibitory concentration (MIC) in µM ranged from 0.03 to 2.34 with 7h having MIC of 0.03 µM against Plasmodium falciparium. The in vitro antibacterial activity of the compounds against some clinically isolated bacteria strains showed varied activities with some of the new compounds showing better activities against the bacteria and the fungi more than the reference drug ciprofloxacin and fluconazole.